The Effectiveness of Village Financial Management in Sukabakti village, Tambelang District, Bekasi Regency - Andini Nurwulandari (Journal of Economics and Business (JECOMBI), 2023)
The purpose of this research is to determine how well finances are managed in Sukabakti Village, which is located in the Tambelang District of the Bekasi Regency. The approach that has been taken is one that is descriptive and qualitative, and the data collection methods that have been utilised include interviews, observations, and documentation studies. Participants in the research included village heads, village administrators, as well as other members of the community who were actively involved in the management of local finances. According to Presidential Regulation Number 43 of 2014, village financial management should include planning, budgeting, administration, reporting, and accountability. The findings of the study indicate that village financial supervision/Village Financial Management in Sukabakti Village is quite effective, with good integrity from the village head and all village officials, transparent and accountable financial governance, as well as active community participation in supervising. Nevertheless, there are still a few roadblocks, such as a dearth of high-caliber human resources and difficulties in the compilation of financial reports. As a result, it is recommended that the government of the Bekasi District provide assistance in the form of training for human resources and the establishment of a more complex